If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + -76 = 128 + x Reorder the terms: -76 + -11x = 128 + x Solving -76 + -11x = 128 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -76 + -11x + -1x = 128 + x + -1x Combine like terms: -11x + -1x = -12x -76 + -12x = 128 + x + -1x Combine like terms: x + -1x = 0 -76 + -12x = 128 + 0 -76 + -12x = 128 Add '76' to each side of the equation. -76 + 76 + -12x = 128 + 76 Combine like terms: -76 + 76 = 0 0 + -12x = 128 + 76 -12x = 128 + 76 Combine like terms: 128 + 76 = 204 -12x = 204 Divide each side by '-12'. x = -17 Simplifying x = -17
| Log(20)=1.3 | | X-9=16-15+3x | | 10x^4-12x^2= | | X+5=10-30+7x | | an=-15+(n-1)(4) | | -3s+-9s+15s=-6 | | xyz-xyz=0 | | X-5-6=6-25-6x | | -3g+-9s+15s=-6 | | f(1)f(x)=6x-5 | | X+5-6=6-25-4x | | 16g+5g-20g=20 | | 49=3x+143 | | 3-(y-2)=3y | | X-7=16-25+3x | | 12h-12h+2h-h=16 | | X+7=16-25+2x | | 4x+1y=9 | | 3(3-5x)+3x=93 | | 23/25-2/5= | | 5abc=99999995 | | y=(2x-1)/(3x-4) | | -8-w=17 | | (x+1)(x+2)(x+3)+1=0 | | -3g=10.5 | | x=(2y-1)/(3y-4) | | 287=(x*4)+19 | | J=.25+d | | V9/15=0 | | (x-2)(x-8)=24 | | J-d=0.25 | | -3x+6=-6x-33 |